Differential immunogenicity in people living with HIV with varying CD4 levels after bivalent mRNA COVID-19 booster vaccination - Napon Hiranburana; Nattakarn Thippamom; Anchalee Avihingsanon; Supaporn Wacharapluesadee; Sasiwimol Ubolyam; Stephen J. Kerr; Chee Wah Tan; Lin-Fa Wang; Opass Putcharoen (PLoS ONE, 2025)
People living with HIV (PLWH) exhibit heterogeneous immune responses, influenced by varying degrees of immune deficiency and viral suppression. The efficacy of COVID-19 vaccines in this population remains underexplored, particularly in those with low CD4 counts. This study assessed the antibody response in PLWH with CD4 T-cell levels ≤200 cells/mm3 compared to those with higher levels, following a bivalent mRNA COVID-19 vaccine booster. All participants were on effective Antiretroviral therapy (ART) with virologic suppression and had received the booster more than a year after their last vaccination. Participants with lower CD4 counts exhibited reduced baseline Anti-RBD IgG titers. However, significant increases in Anti-RBD IgG and surrogate virus neutralization test (sVNT) levels were observed across both CD4 groups post-booster. Despite lower Geometric mean titer (GMT) in the low CD4 group, this group achieved a higher post-boost Anti-RBD IgG Geometric mean ratio (GMR), indicating a robust vaccine response facilitated by effective ART. Nonetheless, cross-neutralization against the circulating XBB variant was limited. Although individuals in the low CD4 group exhibited reduced protection at baseline, they showed significant increase in Anti-RBD IgG and sVNT levels across all CD4 counts after receiving the bivalent COVID vaccine booster.